Chaucer, ethics, and gender - Blamires, Alcuin; Oxford eBooks (Oxford : Oxford University Press, 2006)
Alcuin Blamires explains how Chaucer shapes human problems in terms of the uneasy mix of moral traditions at the time. He looks at the main ethical and gender issues that dominate Chaucer's work.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chaucer, Geoffrey, -- d. 1400 -- Criticism and interpretation; Ethics in literature; Gender identity in literature; Electronic books